Additive Manufacturing for Structures Generated by Topology Optimization - Hui Cin, Chong (IRC, 2017)
Topology optimization is a mathematical approach that deals with determination of connectivity, geometries of cavities and location of voids in the design domain considered. In topology optimization, filtering technique is one of the parameter that affects the topology generated. Due to the difficulty to manufacture complex shapes of optimal layouts, additive manufacturing is the best option to replace traditional manufacturing processes to overcome this barrier. Additive manufacturing is a process of building up the model using layer-by-layer concept. Additive manufacturing provides the design freedom to the users but it has its own limitation too. Hence, this paper aims to fill the gap by relating these two different fields to investigate the impact of different filtering techniques in topology optimization with various build orientation in additive manufacturing. SIMP method was used to compute compliance based topology optimization problem and generate the optimal layouts of three-dimensional beam structures. In the results, sensitivity filter is proposed to be used in topology optimization to achieve minimum compliance as weight reduction can be achieved in the range of 24% to 31%. This significant result can provide possibilities in contributing in aerospace and automotive industry and indirectly help in sustainable development. In future work, effect of mixed filtering techniques can be investigated and use high speed super computer to improve the computational efficiency. In the aspect of additive manufacturing, soluble support material is suggested to be used to ease the post processing work.